Effectiveness and Determinant Factors of Successfull Scalp Cooling in Preventing Chemotherapy Induced Alopecia in Breast Cancer Patients : Literature Review - Cahyono, Hendra Dwi; Irawaty, Dewi (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Background: Chemotherapy induced Alopecia (CIA) is one of the most complained and cause the highest distress in breastcancer patients with chemotherapy. Cryotherapy or Scalp Cooling is an alternative intervention to reduce metabolism ofcytotoxic agents against hair follicle by lowering the temperature of the scalp. Literature that discusses the effectiveness ofCryotherapy in breast cancer patients is still limited.Objective: Summarize and investigate the effect ofCryotherapy on preventing Chemotherapy induced Alopecia in breast cancerpatients and its determinant factors of successfull Cryotherapy .Design: Literature ReviewData Sources: A search was performed by using Ebscohost, Scopus, Science Direct, and ProQuest database from 2009 to 2019for research article.Review methods: A systematic process was used to analyze and extract data include studies using CASP.Result: From 278 articles that have been observed using CASP, only 10 articles match the inclusion criteria. Total respondentsin 10 articles were 1201 breast cancer patients undergoing chemotherapy. All articles used in this study showed positive resultsabout the effect of Cryotherapy on decreasing the severity of Chemotherapy Induced Alopecia (CIA) measured by hairpreservation, hair loss, hair regrowth, and decreasing use a wig or head covering. The importance of continuously monitoringthe patient's condition to manage the side effects caused by Cryotherapy such as headaches, cold, and nausea.Conclusion:Cryotherapy significantly reduce the severity of CIA by inhibit the process of mitosis and vasoconstriction. There are several